Ideas about art - Desmond, Kathleen Kadon (Chichester, West Sussex, U.K. Wiley-Blackwell, 2011)
"Ideas About Art is an intelligent, accessible introductory text for students interested in learning how to think about aesthetics. It uses stories drawn from the experiences of individuals involved in the arts as a means of exposing readers to the philosophies, theories, and arguments that shape and drive visual art. An accessible, story-driven introduction to aesthetic theory and philosophy Prompts readers to develop independent ideas about aesthetics; this is a guide on how to think, not what to think Includes discussions of non-western, contemporary, and discipline-specific theories Examines a range of art-based dilemmas across a wide variety of disciplines - from art and design and law to visual and museum studies"-- Provided by publisher.
"Ideas about Art is an engaging and inspirational text that teaches students to apply critical theory and develop and support their own opinions concerning aesthetics and art theory. The text examines a range of art-based dilemmas, cases and instances of art in a multicultural context and across a wide variety of disciplines--from art and design and law to visual and museum studies. Organized into small chapters that begin with concrete stimuli for delving into deeper philosophical issues real and hypothetical--art's value, taste, the creative process, censorship, and aesthetic taste and theory--Ideas about Art includes stories from artists, art critics, art museum and art gallery professionals and philosophers, and brings art and aesthetics to life"-- Provided by publisher.
Public opinion/public art -- Non-Western ideas -- Western ideas -- Beauty -- Expression & aesthetic experience -- Art & ethics -- Political art, censorship & pornography -- Art & economics -- Feminist art, aesthetics & art criticism -- Postmodern art & attitudes -- Photography & new media -- (Re)discovering design -- Art & aesthetic education -- Artists, art critics, art historians, curators, museums & viewers.
Keywords: Art -- Philosophy; Aesthetics